CURRENT CHALLENGES IN THE DEVELOPMENT AND FORMULATION OF AMORPHOUS SOLIDS - Kumar, Gannu Praveen; Kumar, Bakka Sravan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Interest in amorphous pharmaceutical systems is steadily growing over the last 10 years. The amorphous state is critical in determining the solid state, physical and chemical properties of many pharmaceutical dosage forms. The main reason of the growing interest toward amorphous materials is the need to improve the bioavailability of drugs with poor aqueous solubility. Many drugs exist in crystalline solid form due to reasons of stability and ease of handling during the various stages of drug development. Conversion of the crystalline to amorphous form may occur during various pharmaceutical processes. This could change the dissolution rate and transport characteristics of the drug. The current focus of research in this area is to understand the origins of amorphous forms. The various thermodynamic phenomena such as glass transition, fragility, molecular mobility, devitrification kinetics, molecular level chemical interactions, solubility and stability are critically discussed. The aim of this review is to understand the recent development in the area of amorphous state and to address the current challenges faced by pharmaceutical formulation and process development scientists and thus is mandatory to anticipate future developments.Key words: Crystalline solids, amorphous forms, characterization, stabilization.